Phenotyping and marker based identification of resistant lines in wheat (Triticum aestivum) against spot blotch pathogen (Cochliobolus sativus) - CHOUDHARY, DEVENDRA K; AGGARWAL, RASHMI; BASHYAL, BISHNU MAYA; SHANMUGAM, V; PADARIA, JASDEEP C (The Indian Journal of Agricultural Sciences, 2019)
Spot blotch of wheat caused by Cochliobolus sativus is an emerging disease in hot and humid climate. Breeding for resistance is most suitable approach for management of this disease. A collection of 55 wheat (Triticum aestivum L.) genotypes were phenotyped for spot blotch resistance at seedling and adult plant stages. Based on phenotyping of 10 days old seedling Chirya 7, Chirya 3, Ning 8139, Suzhou, Milan-3, HD 2888, HD 2967, WR 95 were identified as resistant, while genotypes, viz. A-9-30-1, Agra local, C-306, K-68, Sonalika were highly susceptible. Phenotyping of adult plants stage revealed Chirya 7, Chirya 3, Ning 8139, Suzhou, Milan-3, HD 2888, HD 2967, WR 95, HW 3081 as resistant, whereas genotypes A-9-30-1, Agra local, C-306, Sonalika were highly susceptible. Phenotyping in adult and seedling plants showed a strong correlation of r = 0.91. DNA was isolated from all genotypes and was subjected to polymerase chain reaction (PCR) using simple sequence repeat (SSR) primers, viz. Xgwm148, Xgwm374 and Xgwm067, Xgwm371 for QTL Qsb.bhu-2B and Qsb.bhu-5B respectively. Presence and absence of different markers was confirmed by a unique amplification by PCR and visualized in Agarose gel electrophoresis. Two markers Xgwm371 and Xgwm374 showed significant association with resistance to B. sorokiniana and established to be linked with resistance since these were absent in highly susceptible genotypes. Hence, these markers could be useful in increasing the efficiency of selection for resistance to B. sorokiniana in wheat breeding and can be used in marker assisted selection.